PERAN "CAKRUK BACA BERGERAK” DALAM PENGEMBANGAN LITERASI ANAK USIA DINI - Sri Marwiyati; M.Agung Hidayatulloh (AWLADY : Jurnal Pendidikan Anak, 2018)
This paper describes the role of Cakruk Baca Bergerak (Cak Bager) in developing early childhood literacy in RA Miftahul Falah as well as its supporting and inhibiting factors. This qualitative study used observation, interview, and documentation for data collection techniques. Cak Bager contributes positively to children in RA Miftahul Falah. Children free to express themselves by learning to read, write, color, tell stories, and ask questions. Children become closer to books, play with books, even if they just go back and forth to see pictures and tell it to their friends. In addition, Cak Bager also provides activities such as coloring competitions, storytelling, and role playing. Variations in these activities can overcome child boredom so that the purposes of literacy development run well. Literacy development through Cak Bager in RA Miftahul Falah was supported by quite a large collection of books, book grants from the government to managers of Cak Bager, provision of time and place by schools, mentoring teachers and parents to children while in school, and the collaboration of Cak Bager managers with literacy activists. On the other hand, these efforts encountered obstacles in the forms of limited time for visits, lack of facilities and infrastructure for reading at home, and lack of reading culture at home.